Single-Cell Analysis Identifies Distinct Populations of Cytotoxic CD4+ T Cells Linked to the Therapeutic Efficacy of Immune Checkpoint Inhibitors in Metastatic Renal Cell Carcinoma - Yang X; Wu J; Fan L; Chen B; Zhang S; Zheng W (Dove Medical Press, 2024)
Xu Yang,1,* Jianwei Wu,1,* Longlong Fan,2 Binghua Chen,3 Shiqiang Zhang,4 Wenzhong Zheng1 1Department of Urology, Fujian Medical University Union Hospital, Fuzhou, People's Republic of China; 2Department of Urology, The Eighth Affiliated Hospital, Sun Yat-sen University, Shenzhen, Guangdong, People's Republic of China; 3Department of Urology, Pingtan Branch of Fujian Medical University Union Hospital, Fuzhou, People's Republic of China; 4Department of Urology, Kidney and Urology Center, The Seventh Affiliated Hospital, Sun Yat-sen University, Shenzhen, Guangdong, People's Republic of China*These authors contributed equally to this workCorrespondence: Wenzhong Zheng, Department of Urology, Fujian Medical University Union Hospital, 29 Xinquan Road, Gulou District, Fuzhou, Fujian Province, 200001, People's Republic of China, Email wenzhong_zheng@yeah.net Shiqiang Zhang, Department of Urology, Kidney and Urology Center, The Seventh Affiliated Hospital, Sun Yat-sen University, 628, Zhenyuan Road, Guangming Dist, Shenzhen, 518107, People's Republic of China, Email zhangshq55@mail.sysu.edu.cnBackground: The involvement of cytotoxic CD4+ T cells (CD4+ CTLs) and their potential role in dictating the response to immune checkpoint inhibitors (ICIs) in patients with metastatic renal cell carcinoma (mRCC) remains an unexplored area of research.Methods: Utilizing single-cell RNA sequencing, we analyzed the immunophenotype and expression patterns of CD4+ T lymphocyte subtypes in mRCC patients, followed by preliminary validation via multi-immunofluorescent staining. In addition, we obtained a comprehensive immunotherapy dataset encompassing single-cell RNA sequencing datasets and bulk RNA-seq cohorts from the European Genome-Phenome Archive and ArrayExpress database. Utilizing the CIBERSORTx deconvolution algorithms, we derived a signature score for CD4+ CTLs from the bulk-RNA-seq datasets of the CheckMate 009/025 clinical trials.Results: Single-cell analysis of CD4+ T lymphocytes in mRCC reveals several cancer-specific states, including diverse phenotypes of regulatory T cells. Remarkably, we observe that CD4+ CTLs cells constitute a substantial proportion of all CD4+ T lymphocyte sub-clusters in mRCC patients, highlighting their potential significance in the disease. Furthermore, within mRCC patients, we identify two distinct cytotoxic states of CD4+ T cells: CD4+GZMK+ T cells, which exhibit a weaker cytotoxic potential, and CD4+GZMB+ T cells, which demonstrate robust cytotoxic activity. Both regulatory T cells and CD4+ CTLs originate from proliferating CD4+ T cells within mRCC tissues. Intriguingly, our trajectory analysis indicates that the weakly cytotoxic CD4+GZMK+ T cells differentiate from their more cytotoxic CD4+GZMB+ counterparts. In comparing patients with lower CD4+ CTLs levels to those with higher CD4+ CTLs abundance in the CheckMate 009 and 25 immunotherapy cohorts, the latter group exhibited significantly improved OS and PFS probability.Conclusion: Our study underscores the pivotal role that intratumoral CD4+ CTLs may play in bolstering anti-tumor immunity, suggesting their potential as a promising biomarker for predicting response to ICIs in patients with mRCC.Keywords: single-cell analysis, granzyme K and granzyme B, cytotoxic CD4+ T cells, immune checkpoint inhibitors, renal cell carcinoma